FAKTOR AUTENTIK KESULITAN BELAJAR BERBAHASA DALAM PEMBELAJARAN PADA ANAK BERKEBUTUHAN KHUSUS (TUNARUNGU): Authentic Factors of Language Learning Difficulties in Learning For Children With Special Needs (Deafblind) - Ruhul Wahyuni, Andi; Ramly; Haliq, Abdul (Journal of Applied Linguistics and Literature, 2025)
This study aims to analyse the authentic factors of language learning difficulties in children with special needs (deaf) in Grade VIII of SMP SLB Negeri 1 Makassar and how these factors affect language learning difficulties in deaf children. This study uses a qualitative descriptive method with data collection techniques in the form of observation and interviews. In addition, analysis techniques such as transcription, categorisation, theme analysis, and conclusion drawing were used. Based on the results of the study, it can be concluded that the language learning difficulties of deaf students in class VIII of SLB Negeri 1 Makassar are caused by genetic factors, disorders or accidents that have an impact on limited access to hearing aids, a lack of awareness among parents about early education, and a very limited understanding of vocabulary.